Acknowledgement to Reviewers of Veterinary Sciences in 2016 - Veterinary Sciences Editorial Office (Veterinary Sciences, 2017)
The editors of Veterinary Sciences would like to express their sincere gratitude to the following reviewers for assessing manuscripts in 2016.[...]